Las parroquias y el Poder Urbano en Zaragoza durante los siglos XIV y XV - Lozano Gracia, Susana (En la España Medieval, 2006)
A study of the institutional structure of the municipality of Zaragoza, particularly the offices of parish councillor, city councillor and ordinary judge. The role of parishes as districts for elections and assembly within the framework of the city council. Strategies for political promotion and matrimonial alliances among various families at the end of the fourteenth century: Azuara, Canudo, Borau.